Comparative Education for Africa: Perspective from Students ’ Perceptions of and Motivations for Studying Comparative Education - Anangisye, William A. L.; Wolhuter, C. C.; O ' Sullivan, M. (Papers in Education and Development, 2018)
In view of the North-American-Western European hegemony in education and contemporary curriculum theory, which prescribes an input by students as clients, the authors from two African countries, South Africa and Tanzania, surveyed their students about what they expected to gain from a Comparative Education course, and contrasted that with the expectations of students of a European country, Ireland. The comparison revealed startling divergences. Whereas the Irish students ' main expectation was that their Comparative Education course would prepare them for a teaching job abroad, the South African students looked to their Comparative Education course to enlighten the domestic education reform project and to improve their teaching strategies, while the Tanzanian students had a purely intellectual view of the subject €” wanting Comparative Education to contribute to their intellectual moulding and development. The authors relate these differences to contextual differences between Ireland, South Africa and Tanzania, and conclude that contextual factors should be taken into account, when developing Comparative Education courses for universities in Africa.